Retrieval of a spherical foreign body in the right bronchus of a small child - Frasiska, Kadek Devi Ari; Dewantara, I Putu Santhi; Sucipta, I Wayan; Putra, I Dewa Gede Arta Eka; Asthuta, Agus Rudi; Saputra, Komang Andi Dwi; Wiranadha, I Made (PERHATI-KL, 2025)
Background: Bronchial foreign body aspiration can result in life-threatening obstruction of the airway, which makes it a serious emergency, particularly in children. Purpose: To report and discuss the challenges in extracting a spherical foreign body in right bronchus of a small child. Case report: A 3-year-old child, inadvertently inhaled a tiny, metallic ball, which resulted in respiratory distress. Diagnostic evaluation revealed high density opacity on chest X-ray, suggestive of a foreign body in the right main bronchus. The round metallic foreign body was successfully retrieved through bronchoscopy using optical forceps and magnetic forceps. Method: Literature search was conducted using keywords ”round foreign body in bronchus”, ”bronchial foreign body”, and ”bronchoscopy” in Medline and PubMed. Result: A total of 5 cases of round foreign bodies in the bronchus were published from 2003 to 2020. One case reported surgical removal of the foreign body, while 4 others were extracted via bronchoscopic intervention. Discussion: This case underscores the complexities in managing bronchial foreign body aspiration, particularly spherical shaped foreign body. The foreign body was round shaped and metallic, so it was difficult to be grasped, and the patient’s bronchus was very frail. Prompt diagnosis and appropriate interventions, guided by thorough clinical assessment and imaging, are crucial in ensuring favorable outcomes in such cases. Conclusion: In managing patients with foreign bodies in the bronchi, it is essential to select the appropriate instruments depending on the shape and type of foreign body, and surgical intervention should be considered as the last resort for foreign body extraction.